Role of Organic Matter, Iron Oxides and Aluminosilicate Content on Physicochemical Interactions Between Ciprofloxacin and Andisol Soil - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C (Springer Science and Business Media Deutschland GmbH, 2025)
Purpose: The widespread use of antibiotics to treat infectious diseases in humans and animals has raised significant environmental concerns due to their presence in soils. The interaction between natural aluminosilicates such as allophane, both with and without iron oxides (FexOy) and organic matter (OM) coatings, in the adsorption of Ciprofloxacin (CIP) remains still unexplored. The objective of this study is to establish the role of different soil components, OM and FexOy, in the adsorption of CIP in soils. Methods: Santa Bárbara (SB) series soil and chemically treated substrates without OM (SB1) and without OM and FexOy (SB2) were characterized. All CIP adsorption studies were conducted through batch experiments in an electrochemical cell, by using square wave voltammetry to determine CIP concentration. Results: Adsorption isotherms revealed two types of adsorption sites in the SB soil: instantaneous and time dependent. The Langmuir-Freundlich model explained cooperative adsorption, while the Freundlich model aligned with SB1 and SB2 samples. SB1 showed higher adsorption capacity but lower intensity than SB2. The removal of OM and FexOy notably influences the adsorption behavior, resulting in lower capacities than the original SB soil. Conclusions: This study emphasizes the complex interaction between CIP and soil components. The adsorption data highlights the strong binding of CIP to soil particles and substrates, suggesting a low leaching potential. The calculated GUS index of 2.758 further supports this, indicating a moderate leaching potential and reinforcing the importance of understanding the strength of CIP binding in environmental matrices. This knowledge is crucial for assessing its mobility and developing strategies to minimize its environmental impact. © The Author(s) under exclusive licence to Sociedad Chilena de la Ciencia del Suelo 2025.